Planned home birth in low-risk pregnancies - Made Diah Vendita Sakuntari; I Nyoman Hariyasa Sanjaya; Cokorda Istri Mirayani Pemayun; Ni Wayan Dewi Purwanti; Ni Putu Nining Gianni; Ni Luh Made Diah Mas Cahyani Putri; Ni Komang Anik Pirgantari; Ni Luh Md Dwi Laxmi Satriani; Firsta Sesarina Mintariani; Anak Agung Wahyu Putri Agustini; Ketut Widyani Astuti (The Indonesian Society of Perinatology, South Jakarta, Indonesia, 2022)
Introduction: Planned home births are often a safe option for low-risk pregnancies, according to prior studies. This study aims to ascertain the characteristics of planned home deliveries with skilled medical staff in low-risk pregnancies as well as the outcomes on mother and infant health in Denpasar, Bali. Methods: The planned home births from 2010 to 2019 were examined in this study using a retrospective descriptive design. The study included all intended home deliveries, including those that required hospital transfers owing to difficulties. As many as 168 planned home births with private doctor assistance made up the study’s sample. Sociodemographic and clinical variables were both examined in this analysis. Results: The mean age of the sample in this study was 32 years. The findings indicate that women planning a home delivery with a licensed doctor in low-risk pregnancies have a better likelihood of spontaneous vaginal birth and favorable outcomes for maternal health. Additionally, there is a reduced likelihood of hospital transfer (10%). Furthermore, evidence demonstrates that planned home births are typically linked to fetal wellbeing. Conclusion: The majority of women gave birth between 38 and 40 weeks gestation. The majority of samples were deliveries were normal vaginal births. The main reasons for transfer were due to the arrested cervical dilation or the arrested progress of the fetal head.